Does the Arab region have an agrarian question?. Issue 5 (29th July 2021) - Ajl, Max
ABSTRACT: Discussion on food sovereignty and agro-ecology, and Anglophone rural sociology have blind spots when it comes to the Middle East/North African (Arab) region. This article explores them; outlines some initial concepts, discusses avenues for research, and notes some socio-political features of the region which make it distinct from others. It focuses on the necessity to include war and the national question to understand the regional agrarian question and advances and retreats in regional knowledge production. It proceeds by (1) establishing the relative absence of the region from the leading peasant studies journals; (2) synthesizing the region's political economy and waves of knowledge production; (3) highlighting local traditions which speak to the questions of food sovereignty and agro-ecology; and (4) listing a series of theoretical, historical, and analytical avenues which remain to be addressed.